Rule based recommendation system to support crop lifecycle management (The Journal of Modern Project Management, 2022)
Crop lifecycle management is important for crop care and maintenance throughout its life. The existing recommendation and expert systems do not provide advice for the entire crop lifecycle. However, each stage of the crop's lifecycle necessitates a different set of recommendations. As a result, this paper proposed a recommendation system based on sensor data and rule-based extraction from expert people to provide crop management advice throughout its lifecycle. The proposed system's rules are built around IF-THEN situations. The proposed system will analyze the data by searching for relationships between input data and rule-based using a php script to define the best recommendation for farmers. This proposed system was put into action in a greenhouse dome in Chiang Mai, Thailand. Farmers were overwhelmingly pleased with it, giving it a 96% satisfaction rating.